Anticipatory Governance In Land Readiness Policy For Addressing The 2045 Demographic Bonus Surge - Slamet Yuswanto; M.B. Zubakhrum Tjenreng (Faculty of Law, University of Mataram, 2025)
Indonesia’s projected demographic bonus, expected to peak in 2045, presents both an opportunity and a major challenge for land availability to support housing, industrial development, and food security. This study aims to analyze the readiness of government policies in anticipating land demand amid the demographic bonus, identify the gap between existing regulations and empirical conditions, and formulate strategies based on the concept of anticipatory government. The research employs a qualitative descriptive method with a normative juridical approach through a review of policy documents, statutory regulations, and relevant academic literature. The findings reveal that although the government has developed long-term planning documents such as the National Long-Term Development Plan (RPJPD) 2025–2045 and the Grand Design of Population Development (GDPK) 2010–2035, their implementation faces persistent challenges in institutional coordination, regulatory enforcement, and the high rate of productive land conversion. The discrepancy between legal norms and field practices indicates that spatial planning policies remain reactive rather than forward-looking. The proposed anticipatory government strategy encompasses three key dimensions: (1) long-term projections based on demographic and spatial data; (2) policy innovations, including vertical housing and land-use conversion control; and (3) multi-actor participation through collaborative governance. Implementing these strategies is expected to strengthen the integration of spatial planning, food security, and social welfare policies, ensuring that Indonesia’s demographic bonus in 2045 becomes a driver of sustainable development rather than a demographic burden.